PENINGKATAN KEMAMPUAN MAHASISWA MENULIS CERITA ANAK MELALUI STRATEGI MENULIS TERBIMBING - Enny Zubaidah (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2015)
AbstractThis action research study aims to improve students’ skills in writing children’s storiesthrough the guided writing strategy. The research subjects were semester three studentsof PGSD FIP UNY. The data were collected through a pretest and a posttest in each cycle,interviews, observations, field notes, portfolio, and questionnaires. The data were analyzedusing descriptive statistics. The results of the study were as follows. First, the use of theguided writing strategy was capable of improving students’ skills in writing children’sstories. The learning process was implemented by making the students understandelements of a child’s story and language elements through: (a) reading children’s storiesby other writers, (b) discussing strory reading results by analyzing story elements, (c)retelling the stories that had been read, and (d) writing stories independently. Second, thestudents’ skills in writing children’s stories improved in each cycle. Based on the pretestresults, no student (0%) had a high level of skills, 7 students (25.9%) had a moderate levelof skills, and 20 students (74.1%) had a low level of skills. Based on the posttest resultsin Cycle 3, 12 students (44%) had a high level of skills, 15 students (56%) had a moderatelevel of skills, and no student had a low level of skills.Keywords: story writing, schildren’s stories, guided writing strategy